Bacteria producing L-asparaginase isolated from Peruvian saline environments - Montes, Jeanett; Laboratorio de Biología Molecular, Facultad de Farmacia y Bioquímica, Universidad Nacional Mayor de San Marcos, Lima. (2021)
L-asparaginase (EC 3.5.1.1) hydrolyzes L-asparagine in L-aspartic acid and ammonia. Its efficiency is subject to its kinetics and specificity on the substrate, characteristics that vary from one source to another. Thus, microorganisms from saline environments constitute a phylogenetic and metabolically heterogeneous group for the search of new enzymes. Therefore, the objective of this study was the phenotypic and genotypic characterization of bacteria with L-asparaginase activity isolated from Maras, Pilluana and Chilca salterns. The 24 evaluated bacteria were classified as 38% Gram-negative bacilli and 54% positive; and 8% Gram-positive cocci. The majority grew in 5% salt water, pH 7.0 and 37 °C, all assimilated glucose. Of the 24 bacteria that produced L-asparaginase in solid medium, enzymatic activity was determined in submerged cultures by the Nessler method in 14 of them. The CH11, M62, M64, M68, and P19 strains identified as Bacillus sp., by partial sequencing of the 16S ribosomal gene, presented higher L-asparaginase activity and instability due to the presence of proteases. Saline environments bacteria are potential sources for the prospective production of L-asparaginase to use them as a therapeutic agent and in the food industry.